Predictors of Hearing Protection Use among Industrial Workers - Kunlayanee Tantranont (2018)
© American Association of Occupational Health Nurses. Promoting the use of hearing protection devices (HPDs) can prevent noise-induced hearing loss (NIHL) among workers who are exposed to excessive noise. In the present study, the authors examine factors that may explain HPD use among industrial workers from 15 manufacturing plants in Thailand. Participants consisted of 268 randomly selected workers exposed to harmful noise levels for which routine HPD use was required. Logistic regression analysis of study variables revealed the most powerful predictors of HPD use were perceived hearing status (b = 0.66, p <.001) and interpersonal factors (i.e., role modeling and interpersonal support; b = 0.20, p <.001). Together, these variables correctly classified 63.4% of the cases. These findings have implications for interventions aimed at motivating workers to use HPDs regularly.